Prevalence and risk factors of Entamoeba histolytica and Giardia lamblia infection among patients with gastrointestinal complaints - Hussein A. Sadeq; Shivan O. Haydar; Ghanem M. Jaafar; Mohammad I. Alberfkani (Faculty of Medicine, Universitas Trisakti, 2026)
BackgroundIntestinal parasitic infections remain a significant public health problem in developing regions, primarily driven by inadequate hygiene and sanitation standards. The most prevalent protozoan parasites causing gastrointestinal illness are Entamoeba histolytica and Giardia lamblia. This study aimed to investigate the prevalence of these infections and evaluate their association with socio-demographic factors and clinical stool consistency. MethodsA total of 122 subjects aged 1-60 years were involved in this cross-sectional study. Data was collected via direct interviews and parasitological diagnosis using standard laboratory protocols to identify the presence of cysts or trophozoites. Data were stratified by age group, gender, and stool consistency, and a Chi-square test was used for data analysis. ResultsThe findings revealed a high overall prevalence, with E. histolytica being the main parasite at 84.42% (103/122) compared to G. lamblia at 15.57% (19/122). Age-specific data showed that the 31-40 year age group had the highest infection rate for E. histolytica (92.31%), while the 21-30 year age group showed the highest occurrence of G. lamblia (25.81%). Gender-wise, males exhibited a significantly higher infection rate for E. histolytica (91.93%) compared to females (76.66%) (p=0.038). Regarding stool consistency, a highly significant association was observed (p<0.001). ConclusionThe study highlights a substantial burden of protozoan infections, particularly E. histolytica. The significant association between stool consistency and parasite type emphasizes the importance of clinical presentation in diagnostic suspicion. Enhanced community-level health education and improved sanitation infrastructure are urgently needed to mitigate the transmission of these intestinal parasites.